2020
DOI: 10.3389/fgene.2020.00373
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Genetic Variation of BMI, Body Composition, and Fat Distribution for Mental Traits and Disorders: A Look-Up and Mendelian Randomization Study

Abstract: Anthropometric traits and mental disorders or traits are known to be associated clinically and to show genetic overlap. We aimed to identify genetic variants with relevance for mental disorders/traits and either (i) body mass index (or obesity), (ii) body composition, (and/or) (iii) body fat distribution. We performed a look-up analysis of 1,005 genomewide significant SNPs for BMI, body composition, and body fat distribution in 15 mental disorders/traits. We identified 40 independent loci with one or more SNPs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
2
4

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 151 publications
(219 reference statements)
1
18
2
4
Order By: Relevance
“…Die Mehrzahl der Loci war mit Schizophrenie, Bildungsstand und/oder Intelligenz verbunden, weniger Assoziationen ergaben sich für bipolare Störungen, Neurotizismus, ADHS, Depression, depressive Symptome und Wohlbefi nden. In dieser Look-up-Analyse war keiner der 1005 berücksichtigten SNPs nach Korrektur für multiples Testen signifi kant mit dem Risiko für Anorexia nervosa assoziiert (Peters et al, 2020). Diese Ergebnisse können einen Hinweis darauf liefern, welche gemeinsamen Mechanismen bei der Entstehung von Adipositas und psychischen Störungen eine Rolle spielen könnten.…”
Section: Genetische Korrelationenunclassified
See 2 more Smart Citations
“…Die Mehrzahl der Loci war mit Schizophrenie, Bildungsstand und/oder Intelligenz verbunden, weniger Assoziationen ergaben sich für bipolare Störungen, Neurotizismus, ADHS, Depression, depressive Symptome und Wohlbefi nden. In dieser Look-up-Analyse war keiner der 1005 berücksichtigten SNPs nach Korrektur für multiples Testen signifi kant mit dem Risiko für Anorexia nervosa assoziiert (Peters et al, 2020). Diese Ergebnisse können einen Hinweis darauf liefern, welche gemeinsamen Mechanismen bei der Entstehung von Adipositas und psychischen Störungen eine Rolle spielen könnten.…”
Section: Genetische Korrelationenunclassified
“…Aufgrund dieser unklaren Datenlage haben wir eine ergänzende two-sample-MR-Studie durchgeführt, die nicht allein auf eine diagnostizierte majore Depression, sondern Eff ekte auf depressive Symptome im Allgemeinen fokussierte (Libuda et al, 2019 (Peters et al, 2020). Die Look-up-Analyse ergab, dass Assoziationen zwischen psychischen Störungen bzw.…”
Section: Genetische Korrelationenunclassified
See 1 more Smart Citation
“…Compared to antipsychotics, weight gain with antidepressants is generally more modest or mild, and differences between antidepressants are small ( 1 , 24 ) ( Table 1 ). Considering antidepressants in patients with MDD, long-term use (>6 months) and polypharmacy of antidepressants, such as the tricyclic antidepressant (TCA) amitriptyline, the tetracyclic mirtazapine and the selective serotonin reuptake inhibitor (SSRI) paroxetine have been associated with weight gain of up to 2.7 kg ( 25 28 ).…”
Section: Obesitymentioning
confidence: 99%
“…Peters et al. ( 24 ) identified 40 loci which may contribute to genetic overlaps between mental disorders/traits and BMI and/or shape related phenotypes. Although a recent study of combined GWAS data from 1,380,284 individuals demonstrated an extensive genetic overlap between BMI and SMI, a different genetic liability to weight gain across these disorders seems to exist.…”
Section: Obesitymentioning
confidence: 99%